2022
DOI: 10.31756/jrsmte.113si
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Middle School Mathematics Teachers’ Beliefs and Goals Regarding a Dynamic Tool in Mathematics Lessons: Case of GeoGebra

Abstract: Currently, teaching with technology has become crucial. This case study investigated the beliefs and goals of four middle school mathematics teachers regarding a dynamic mathematics software: GeoGebra. The participants of the study were four mathematics teachers working in public middle schools in Turkey. The data was collected through semi-structured interviews, lesson observations and perceived technology, pedagogy and content knowledge surveys. Data analysis revealed a consensus on GeoGebra’s usefulness in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…The results of this study show that most users hold favourable views of GeoGebra and find it an effective pedagogical tool. Most researchers found that users have positive perspectives and perceptions about using GeoGebra (Owusu et al, 2023;Saralar-Aras, 2022;Bedada & Machaba, 2022;Handayani et al, 2022;Manganyana et al, 2020;Rafi & Sabrina, 2019;Machromah et al, 2019;Belgheis & Kamalludeen, 2018). Users believe that this software can enhance their understanding of mathematics concepts and increase their motivation and performance in learning mathematics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study show that most users hold favourable views of GeoGebra and find it an effective pedagogical tool. Most researchers found that users have positive perspectives and perceptions about using GeoGebra (Owusu et al, 2023;Saralar-Aras, 2022;Bedada & Machaba, 2022;Handayani et al, 2022;Manganyana et al, 2020;Rafi & Sabrina, 2019;Machromah et al, 2019;Belgheis & Kamalludeen, 2018). Users believe that this software can enhance their understanding of mathematics concepts and increase their motivation and performance in learning mathematics.…”
Section: Discussionmentioning
confidence: 99%
“…This software is among the most important ones in Malaysia's high school mathematics curriculum (Za'ba et al, 2020). Other than Malaysia, it also is widely use in the many countries such as Indonesia (Diva et al, 2023), South Africa (Manganyana et al, 2020), Austria (Weinhandl et al, 2020), and Turkey (Saralar-Aras, 2022). Its use all over the world is due to the fact that this software is free without requiring a licence and is easy to use compared to other mathematics education software.…”
Section: Introductionmentioning
confidence: 99%